Sections of Synonymy in Languages: A comparative Linguistic Study - Ishaq, Sharara Yousif; Obaid, Haider Hasan (Al-Adab Journal, 2022)
Synonymy is a linguistic phenomenon that occurs in all languages, and this phenomenon is closely related to the account of modern linguistic sciences, and it is one of the important phenomena that introduces students to the common parameter of expressions, in addition to the common relations in distinguishing words that are related to each other; According to the semantic division that affects the meaning of the words in these contexts. It is an ancient phenomenon that arose with the emergence of language. It was diagnosed by the ancients to it in their books and books, but it was not recorded until after a while. A disagreement was found among scholars about the phenomenon and they were divided into a research team that was taken into account in determining the synonym and its concept.